Assessment of cooling technologies for solar photovoltaic panels accounting for local solar irradiance and ambient temperature conditions - Lucas, M.; Celis, C. (American Society of Mechanical Engineers (ASME), 2022)
The growing energy demand and climate change emphasize the need to continuously use environmentally friendly energy sources. Consequently, renewable energy sources such as solar energy, which relies on the use of photovoltaic modules, have become popular in recent years. Photovoltaic (PV) modules convert the incident solar irradiance to electric energy. In such devices, by reducing the operating temperature, the associated solar energy conversion efficiency can be increased, and their lifetime extended. Accordingly, to compare their impact on the performance of PV modules, three different cooling methods, all of them coupled to a thermoelectric (TE) generator, (i) natural cooling, (ii) forced air cooling, and (iii) water cooling, are assessed. To evaluate the referred cooling methods, a computational model describing the behavior of the studied cooling methods is initially developed. Then, a PV model accurately predicting the behavior of commercial PV modules is developed and coupled to the cooling methods one. Finally, accounting for local ambient conditions and system operation over the course of one year, several simulations of PV modules with and without cooling systems are carried out using the developed tool. The main results indicate that some cooling techniques are adequate for some months of the year only, whereas the others do so for the remaining months. Indeed, PV module temperature reductions of up 7.7% and system efficiencies of up to 17.2% are observed. One of the particularities of this work relates to the use of local ambient conditions and system operation over a whole operating year.
Keywords: Photovoltaic system; Solar irradiance; Renewable energy; Environmental science; Irradiance; Solar energy; Active cooling; Water cooling; Passive cooling; Nuclear engineering; Automotive engineering; Meteorology; Mechanical engineering; Engineering; Electrical engineering; Physics; Optics; Thermal; https://purl.org/pe-repo/ocde/ford#2.04.00